Cutting decaying bodies: Micro-morphometric analysis of cut-marks on Mesolithic-Neolithic human remains from Lepenski Vir and Vlasac, Serbia. (December 2016) - Wallduck, Rosalind; Bello, Silvia M.
Abstract: At the Mesolithic-Neolithic sites (9500–5500 cal BCE) of Lepenski Vir and Vlasac in the Danube Gorges of Serbia, numerous disarticulated human remains were unearthed along with articulated skeletons. In many cases primary burial was only a temporary stage in the funerary ritual and skeletonised bodies were exhumed, manipulated, and re-located. The majority of bodies were left to decay within the ground prior to exhumation and disarticulation. In some instances, however, the presence of cut-marks indicates that human intervention occurred before completion of the natural decay process. In this paper we present frequency, distribution and micro-morphometric analyses of cut-marks on disarticulated human bones from Lepenski Vir and Vlasac. The use of a Focus Variation Microscope (the Alicona 'InfiniteFocus') has enabled 3-dimensional quantitative analyses of cut-mark characteristics. The location and infrequency of cut-marks strongly suggest that active defleshing was not a systematic part of funerary ritual at these sites, but it more likely occurred on bodies that were accidentally unearthed prior to skeletonisation. Based on the micro-morphometric analysis, discernible and measurable differences exist between different cutting practices and we now better understand the ways in which human bodies were treated. Taking into account other taphonomic observations, we suggest that cutting occurred on partially decomposed bodies. Highlights: Frequency, distribution and micro-morphometric analysis of cut-marks on human bones from Lepenski Vir and Vlasac (Serbia). There are discernible and measurable differences between cutting practices. Cutting after a period of decay is inferred once other taphonomic evidence is incorporated.